Transformation of a Silent Adrencorticotrophic Pituitary Tumor Into Central Nervous System Melanoma - Brandon A. Miller MD, PhD; Tomoko Tanaka MD; Adriana G. Ioachimescu MD, PhD; Cristina Vincentelli MD; Christina L. Appin MD; Nelson M. Oyesiku MD, PhD (SAGE Publishing, 2013)
Silent adrenocorticotrophic pituitary adenomas are nonfunctioning pituitary adenomas that express adrenocorticotrophic hormone (ACTH) but do not cause the clinical or laboratory features of hypercortisolemia. Primary central nervous system (CNS) melanoma is well documented, but rarely originates in the sellar region or pituitary gland. Here we report transformation of an aggressive silent adrenocorticotrophic pituitary adenoma that transformed into CNS melanoma and review other presentations of pituitary melanoma. A 37-year-old woman initially presented with apoplexy and an invasive nonfunctioning pituitary macroadenoma for which she underwent transphenoidal surgery. The patient underwent 3 subsequent surgeries as the tumor continued to progress. Pathology from the first 3 operations showed pituitary adenoma or carcinoma. Pathology from the final surgery showed melanoma and the magnetic resonance imaging characteristics of the tumor had changed to become consistent with CNS melanoma. Dermatologic and ophthalmologic examinations did not identify cutaneous or ocular melanoma. The patient's disease progressed despite aggressive surgical, medical and radiologic treatment. To our knowledge, this is the first report demonstrating transformation of a primary pituitary tumor into melanoma. The mechanism of tumor transformation is unclear, but it is possible that a mutation in the original ACTH-producing tumor lead to increased cleavage of pro-opiomelanocortin or ACTH into α-melanocyte-stimulating hormone, which in turn stimulated the expression of microopthalmia transcription factor, leading to melanocytic phenotype transformation.